The Effect of Water- and Ultrasonic Bath Systems on Bioactive Compounds and Fatty Acid Compositions of Unroasted and Roasted Pumpkin Seeds - Isam A. Mohamed Ahmed; Mehmet Musa Özcan; Nurhan Uslu; Emad Karrar; Fahad Aljuhaimi (Foods)
In this study, the effects of water bath and ultrasonic bath systems on bioactive properties, phenolic components and fatty acid profiles of unroasted and roasted pumpkin seeds were investigated. It is thought that determining the bioactive components, phenolic constituents and fatty acid profiles of unroasted and roasted pumpkin seeds will lead to the establishment of usage norms according to their composition characteristics. Total phenolic quantities of the pumpkin seed extracts obtained by water bath extraction of the seeds were defined to be between 7.58 (control) and 11.55 (25 min) and 10.20 (control) and 17.18 mg GAE/100 g (50 min), respectively. Phenolic content increased by 50% after 50 min of ultrasonic extraction, indicating the efficiency of this method. Also, total flavonoid amounts increased about 55% after 25 min of ultrasonic extraction, indicating the efficiency of this method. It was observed that the catechin contents of unroasted pumpkin seeds obtained in water and ultrasonic baths decreased significantly at the 50th minute of extraction compared to the control. The antioxidant activity values (DPPH) of roasted pumpkin seeds treated in water- and ultrasonic bath systems increased by approximately 10% compared to the control at 50 min of sonication in both systems, respectively. Also, the 3,4-dihydroxybenzoic acid amounts of the extracts obtained by both extraction systems of roasted pumpkin seeds were determined between 9.85 (50 min) and 17.22 mg/100 g (control) and 11.17 (25 min) and 13.74 mg/100 g (50 min), respectively. The linoleic acid amounts of unroasted pumpkin seed oils extracted in water- and ultrasonic baths varied between 52.34 (50 min) and 53.33% (control) to 52.90 (50 min) and 53.04% (control), respectively. The linoleic acid values of the roasted pumpkin seed oils were established to be between 52.30 (50 min) and 52.84 (25 min) and 52.32 (50 min) and 53.46% (25 min), respectively. In general, the phenolic compound amounts of roasted pumpkin seeds were higher than those of unroasted ones. The fatty acid amounts of pumpkin seed oils extracted with an ultrasonic bath were generally slightly higher than those extracted with a water bath. In future studies, changes in the phytochemical and bioactive properties of pumpkin seed oils obtained by applying different roasting techniques and extraction methods will be investigated.